Fostering social mobility and employability: the case for peer learning. Issue 3 (3rd April 2023) - Donald, William E.; Ford, Neil
ABSTRACT: Higher education institutions continue to face challenges in fostering social mobility and preparing their students for the world of work. The COVID-19 pandemic exacerbated these challenges via disruption to education and reduced opportunities for work-integrated learning. Framing this as our point of departure, we propose that peer learning can play an integral part in reducing the attainment gap by promoting learner autonomy. Our essay uses the example of Supplemental Instruction to highlight the benefits and challenges of peer learning. We end with a call for empirical research and knowledge sharing to advance peer learning in an impactful way.